Adaptive Immunity: New Aspects of Pathogenesis Underlying Neurodegeneration in Glaucoma and Optic Neuropathy - Jiang, Shuhong; Kametani, Marie; Chen, Dong Feng (Frontiers in Immunology, 2020)
Glaucoma is a globally unmet medical challenge and the most prevalent neurodegenerative disease, which permanently damages the optic nerve and retinal ganglion cells (RGCs), leading to irreversible blindness. Present therapies target solely at lowering intraocular ocular pressure (IOP), a major risk factor of the disease; however, elevated IOP is neither necessary nor sufficient to cause glaucoma. Glaucomatous RGC and nerve fiber loss also occur in individuals with normal IOP. Recent studies have provided evidence indicating a link between elevated IOP and T cell-mediated autoimmune responses, particularly that are specific to heat shock proteins (HSPs), underlying the pathogenesis of neurodegeneration in glaucoma. Reactive glial responses and low-grade inflammation may initially represent an adaptive reaction of the retina to primary stress stimuli; whereas, sustained and excessive glial reactions lead to expanded immune responses, including adaptive immunity, that contribute to progressive neural damage in glaucoma. Emerging data suggest a similar mechanism in play in causing neurodegeneration of other forms of optic neuropathy, such as that resulted from acute ischemia and traumatic injuries. These studies may lead to the paradigm shift and offer a new basis for the development of novel mechanism-based diagnosis, therapy, and preventive interventions for glaucoma. As HSPs are induced under various conditions of neural stress and damage in the brain and spinal cord, these findings may have broader implications for our elucidating of the etiology of other neurodegenerative disorders in the central nervous system.